Review of factors influencing the coach-athlete relationship in Malaysian team sports - Murugeesan, Yokananthini; Mohd Hasan, Nurul 'Ain (2015)
Previous research has found that interaction processes between coach and athlete have always been the strongest factor for sports performance. Other researches have drawn conclusions to other factors in the coach-athlete relationship, such as culture and gender. Research has generally shown that effective communication required the development of trust and respect between coach and athlete (Yukelson, 1984). The review focuses on an analysis of past literature on communication styles, culture, and gender as potential key factors influencing the coach-athlete relationship. This review paper examined studies specific to the empirical studies on athletes and coaches from the Western and Asian perspectives. In particular, the review analysed empirical studies on communication, gender and culture as potential factors influencing the coach-athlete relationship. The review concluded that while various studies on the coach-athlete relationship had been done, a majority of the empirical studies were within Western perspectives. Such empirical study is particularly under-researched in Malaysia. Therefore, the paper concludes by suggesting that future research which explores the aspects of communication styles, culture, and gender within the Malaysian context is timely.